The Role of Representational Meaning of Images in Supporting Ideational Meaning in English in Mind: Students’ Book - Kartika Cahyani, Fransisca Putri; Rukmini, Dwi; Wuli Fitriati, Sri (Universitas Negeri Semarang, 2021)
Textbooks have an essential function to guide students’ activities in learning English language and also to provide the materials for teachers in teaching English language. In a textbook, a text is also accompanied by images which can be used to explain the content of the text, or the function of the image is to make the text understandable for the readers. This study investigated visual metafunctions of the images in supporting linguistics metafunction of the texts in students’ textbook. The objectives of this study were to explain the representation of representational meanings of the images in supporting the ideational meanings of the texts. Using the framework of Grammar of Visual Design by Kress and Van Leeuwen (2006) and Systemic Functional Linguistics by Halliday (1994) and Eggins (2004), this study used discourse analysis as the research approach. The source was reading texts in English in Mind: Students’ Book on Culture in Mind sections. The objects of this study was reading texts which were supported by images. The units were clauses in reading texts and visual items, including vectors, colours, image acts, gazes, size of frames and social distance of the images.The findings revealed that the representational meanings of the images supported the ideational meanings of the texts because the images tried to give depiction of the verbal texts to make the readers could comprehend the texts easily. The presence of narrative representational meaning and the presence of material process inform the situation happened in the stories.